Detection of vanC1 gene transcription in vancomycin-susceptible Enterococcus faecalis - Moura, Tiane Martin de (2013)
Here we report the presence and expression levels of the vanC1 and vanC2/3 genes in vancomycin-susceptible strains of Enterococcus faecalis. The vanC1 and vanC2/3 genes were located in the plasmid DNA and on the chromosome, respectively. Specific mRNA of the vanC1 gene was detected in one of these strains. Additionally, analysis of the vanC gene sequences showed that these genes are related to the vanC genes of Enterococcus gallinarum and Enterococcus casseliflavus. The presence of vanC genes is useful for the identification of E. gallinarum and E. casseliflavus. Moreover, this is the first report of vanC mRNA in E. faecalis.